Identification of biomarkers associated with ferroptosis in macrophages infected with Mycobacterium abscessus using bioinformatic tools. - Jiahua Qian; Chenghua Lu; Kai Meng; Zhihong Xu; Honghao Xue; Weijie Yang (PLoS ONE)
Mycobacterium abscessus is a rapidly growing nontuberculous mycobacterium that causes severe pulmonary infections. Recent studies indicate that ferroptosis may play a critical role in the pathogenesis of M. abscessus pulmonary disease. We obtained gene expression microarray data from the Gene Expression Omnibus database, focusing on THP-1-derived macrophages infected with M. abscessus and uninfected controls. Differentially expressed genes related to ferroptosis were identified through weighted gene co-expression network analysis and the "limma" package, followed by gene set variation analysis and gene set enrichment analysis for enrichment assessment. To explore regulatory network relationships among hub genes, we constructed RBP-mRNA, ceRNA, and TF-mRNA networks. Additionally, a protein-protein interaction network was built, and functional enrichment analyses were conducted for the hub genes. The diagnostic value of these genes was assessed using receiver operating characteristic curves. Six differentially expressed genes associated with ferroptosis were identified in M. abscessus infection. The receiver operating characteristic curves demonstrated that these genes had excellent predictive value for the infection. Functional enrichment analysis showed that these genes were involved in immune responses, inflammation, cellular metabolism, cell death, and apoptosis. Pathway enrichment analysis revealed significant enrichment in pathways related to apoptosis, inflammation, and hypoxia. The RBP-mRNA network highlighted significant interactions between hub genes and key RNA-binding proteins, while the ceRNA network predicted that miRNAs and lncRNAs regulate ferroptosis-related genes NACC2 and ITPKB. Furthermore, interactions between the hub gene HSD3B7 and transcription factors LMNB1 and ASCL1 may promote ferroptosis in macrophages by influencing iron metabolism and reactive oxygen species production, contributing to the M. abscessus infection process. Our findings identified biomarkers linked to ferroptosis in M. abscessus infection, providing new insights into its pathogenic mechanisms and potential therapeutic strategies.